전방향성 선형 압전 액추에이터의 설계와 분석 - 정우석; 강종윤; 김정도; 조봉희; 김영호; 윤석진; 백동수 (한국센서학회, 2009)
In this paper, we present design and analysis of the omni-directional linear piezoelectric actuator which was consisted of one actuator using the half-wave vibrator. Through calculating vibration speeds on each sector of the actuator, the displacement of contact point of the actuator is theoretically confirmed to be about 33 nm. To confirm an applicable possibility of omni-directional linear piezoelectric actuator, elliptical motion for linear movement, displacement of the tip, changing directions and admittance characteristics are simulated by ATILA. Compared with theoretical result, we obtained similar data with displacement of 32.5 nm at contact point. And then the actuator is simulated elliptical trajectories for linear motions and changing directions according to combination of input signal.